Hop on Pop - Seuss, Dr. (New York : Beginner Books, 1963)
Presents a Dr. Seuss classic that shows how some one-syllable words with a variety of vowel sounds go together.
K-3
190L
J
1.2
Keywords: Stories in rhyme; Nonsense verses; Readers (Elementary)